Roteiro metodológico para o planejamento de zona de amortecimento em unidades de conservação - Perello, Luís Fernando Carvalho (Universidade Federal de São Carlos, 2011)
The buffer zones around protected areas are often suggested as complementary areas of conservation, but are rarely evaluated. In Brazil, the buffer zones are treated as secondary theme and when deployed, their perimeters are arbitrated. The lack of a script, but also specific regulations for the planning of buffer zones limit the ability to include this territory in the process of organizing conservation. This study aimed to review the legal and ecological principles that have guided the establishment of buffer zones; propose a roadmap based on ecological criteria for buffer zones to plan and implement the proposed method for establishing the buffer zone of National Park Pond Fish, Mostardas, RS. To define the perimeter of the zone, the script relies on the conservation objectives of protected area, the impacts that threaten these goals and structure of the surrounding landscape, identifying conservation opportunities. This information was treated quantitatively using a GIS and spatialized generating scenarios for discussion and the perimeter of the most appropriate choice. The method favors the participation of local communities in decision-making, encouraging the creation of spaces to be exercised co-management of the buffer zone and protected area itself. Using the model created a buffer zone for the National Park of Lagoa do Peixe, mustards, RS, even contemplating a range of marine protection. The buffer zone proposal adds an area around the unit with approximately 150,000 hectares, complementing and supplementing more than 33,000 hectares of habitat for conservation of interest. The model showed, among other things, that landscape structure plays an important role in defining the perimeter of the buffer zone. The adoption of the roadmap should fill an important gap in conservation planning, especially with regard to zoning of protected areas.
Methodological guideline for the planning of the buffer zone in protected areas
Keywords: Ecologia; Zoneamento; Área de proteção ambiental; Conservação da biodiversidade; Unidades de conservação; Parque Nacional da Lagoa do Peixe; Conservation of biodiversity zoning protected areas; Conservation areas; National parks; National Park Lagoon Fish; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS